Theranostic MRI: the future for Type 1 diabetes management?. (February 2014) - Wang, Ping; Moore, Anna
Diabetes mellitus is the most common metabolic disorder worldwide. Type 1 diabetes mellitus results from the lack of insulin production induced by autoimmune destruction of pancreatic β-cells. Theranostic MRI is an emerging field that uses nanometer-scale materials to provide diagnostic insight with simultaneous treatment. These nanoparticle platforms can accommodate targeting ligands, therapeutic moieties, along with complementary imaging modalities for targeted therapeutic goals, while achieving highly accurate multimodality imaging. In this review, we summarize various types of nanocarriers that have been explored for theranostic imaging. We also outline recent progress in theranostic MRI for Type 1 diabetes management. Finally, we discuss future considerations and opportunities afforded by theranostic imaging as a new platform in this field.